ECO-EFFICIENCY, GREEN INNOVATION DAN CARBON EMISSION DISCLOSURE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN INDUSTRI HIGH PROFILE - Sunarto - -; Yanti -; Ade Trisyanto (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2024)
This study aims to determine the effect of eco efficiency, green innovation and carbon emission disclosure on company value in high profile industrial companies listed on the Indonesia Stock Exchange in 2018-2022. The sampling technique in this research used purposive sampling. The analytical technique used in the research is multiple linear regression analysis with the analysis tested namely classical assumptions which include normality tests, multicollinearity tests, autocorrelation tests and heteroscedasticity tests. Hypothesis testing consists of analysis of the coefficient of determination, partial test (t) and simultaneous test (f). The research population is high profile industrial companies for the 2018-2022 period with a sample size of 110 data. The study results show that partially eco-efficiency has no effect on company value, green innovation has an effect on company value, carbon emissions disclosure has an effect on company value and simultaneously eco-efficiency, green innovation and carbon emissions disclosure have an effect on company value.